Low latency breathing frequency detection and monitoring on a personal computer - Leskovsek, Matevz; Ahlin, Dragomira; Cancer, Rok; Hosta, Milan; Enova, Dusan; Pusenjak, Nika; Bunc, Matjaz (Journal of medical engineering & technology, 2011)
We demonstrate a low latency respiratory/breathing frequency detection system that is fast (<5 ms), easy to operate, requires no batteries or external power supply and operates fully via computer-standard USB connection. Exercises in controlling ones breathing frequency, usually referred to as paced-breathing exercises, have shown positive effects in treating pulmonary diseases, cardiovascular diseases and stress/anxiety-related disorders. We developed a breathing frequency detection system which uses two pairs of microphones to detect exhalation activity, eliminate noise from the environment and stream the recording data via USB connection to a personal computer. It showed 97.1% reliability (10 subjects) when monitoring breathing activity in non-guided free breathing and 100% reliability (10 subjects) when monitoring breathing activity during interactive paced-breathing exercises. We also evaluated the breathing frequency detection systems noise elimination functionality which showed a reduction of 84.2 dB for stationary (white noise) and a reduction of 79.3 dB for non-stationary (hands clapping) noise.